Plug in battery electric car : design and integration of rear subframe and related systems - Muhammad Redzuan Sulaiman (2014)
The interest in electric cars has been revived due to rising concerns regarding carbon emission, together with the growing need to reduce the reliance on crude oil. Clean technology of electric cars has proved to become an increasingly attractive option as less pollution is contributed. The threat of global warming has also forced automotive manufacturers to a more viable, eco-friendly solution.